Intra-annual Dynamics of Xylem Formation in Liquidambar formosana Subjected to Canopy and Understory N Addition - Zhang, Shaokang; Rossi, Sergio; Huang, Jian-Guo; Jiang, Shaowei; Yu, Biyun; Zhang, Wei; Ye, Qing (Frontiers in Plant Science, 2018)
Increasing N deposition caused by intensive anthropogenic activities is expected to affect forest growth. However, the effects of N deposition on trees are still controversial due to the wide variability in results and experimental methods used. We conducted an experiment involving both canopy and understory N addition to investigate the effects of N-addition on intra-annual xylem formation of Chinese sweetgum (Liquidambar formosana) in a warm-temperate forest of Central China. Since 2013, 50 kg N ha-1 yr-1 (2.5 times the current natural N deposition) was applied monthly from April to December. In 2014 and 2015, timing and dynamics of xylem formation were monitored weekly during March-December by microcoring the stems of control and treated trees. Similar dynamics of wood formation were observed between canopy and understory N addition. Xylem formation of all the experimental trees started in March and lasted for 119-292 days. Compared to the control, no change was observed in the timing and dynamics of wood formation in N-treated trees. Tree ring-width ranged between 1701 and 4774 μm, with a rate of xylem production of 10.52-26.64 μm day-1. The radial growth of trees was not modified by the treatments. Our findings suggest that short-term N addition is unable to affect timings and dynamics of xylem formation in Chinese sweetgum in Central China. The effects of N on tree growth observed in previous studies might be related to the duration of the experiment or the imbalance between the amount of natural deposition and N added during treatments.